2021
DOI: 10.1371/journal.pone.0250514
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the microbial diversity and structure in a full-scale municipal wastewater treatment plant with particular regard to Archaea

Abstract: Due to limited description of the role and diversity of archaea in WWTPs, the aim of the study was to analyze microbial community structures and diversities with particular regard to Archaea in the samples taken from different stages of the full-scale municipal wastewater treatment plant and effluent receiving water (upstream and downstream discharge point). Our study was focused on showing how the treatment processes influenced the Eubacteria and Archaea composition. Alpha and Beta diversity were used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…1b). The higher diversity of microbial communities in the outlet of the wastewater treatment plant indicates that the treatment process effectively removes pollutants and facilitates the growth of diverse microbial communities [33,34]. Previous studies have reported similar findings, supporting the idea that wastewater treatment processes can enhance microbial diversity in effluent.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…1b). The higher diversity of microbial communities in the outlet of the wastewater treatment plant indicates that the treatment process effectively removes pollutants and facilitates the growth of diverse microbial communities [33,34]. Previous studies have reported similar findings, supporting the idea that wastewater treatment processes can enhance microbial diversity in effluent.…”
Section: Resultssupporting
confidence: 61%
“…Previous studies have reported similar findings, supporting the idea that wastewater treatment processes can enhance microbial diversity in effluent. For instance, a study by Płaza et al [33] investigated the microbial communities in WWTP and found that the treated effluent displayed different microbial diversity compared to the influent. The higher microbial diversity observed in the outlet of the wastewater treatment plant has significant implications for ecosystem health.…”
Section: Resultsmentioning
confidence: 99%
“…During the sampling campaigns, 30 grab samples were collected in the sampling points presented in Figure 1 . The sampling and transportation procedures used are described by Rolbiecki et al [ 22 ] and Płaza et al [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing results were uploaded to the MetaGenome Rapid Annotation Subsystems Technology (MG-RAST version 4.0.3) server as FASTQ files for analysis [ 24 ]. Details of the metagenomic analysis are presented in the paper by Płaza et al [ 23 ]. The sequences were submitted to NCBI database, and they are under BioProject number ID: PRJNA666519.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that pretreatments strengthened its position in the dominant genus. Methanoculleus can use ethanol and some secondary alcohols as electron donors, as they produce methane [37]. This is also one of the important reasons for increasing methane production.…”
Section: Methanogenic Archaeal Community For Different Pretreatmentsmentioning
confidence: 99%